2005
DOI: 10.1016/j.devcel.2005.07.002
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Function of the C. elegans Ortholog of TPX2 Is to Localize Activated Aurora A Kinase to Mitotic Spindles

Abstract: In vertebrates, the microtubule binding protein TPX2 is required for meiotic and mitotic spindle assembly. TPX2 is also known to bind to and activate Aurora A kinase and target it to the spindle. However, the relationship between the TPX2-Aurora A interaction and the role of TPX2 in spindle assembly is unclear. Here, we identify TPXL-1, a C. elegans protein that is the first characterized invertebrate ortholog of TPX2. We demonstrate that an essential role of TPXL-1 during mitosis is to activate and target Aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
104
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 47 publications
10
104
0
Order By: Relevance
“…This result is consistent with the earlier observations that, both in egg extract and in cells, bipolar spindle formation can proceed without centrosomes, presumably via the chromatin/RanGTP/TPX2-mediated pathway (24,30,31). By contrast, and as expected (13,14,25,27,32), TPX2-depleted extract was inactive in RanGTP-driven MT assembly, while supporting AurA recruitment to and MT nucleation by centrosomes (Fig. 2F, i and iii and Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This result is consistent with the earlier observations that, both in egg extract and in cells, bipolar spindle formation can proceed without centrosomes, presumably via the chromatin/RanGTP/TPX2-mediated pathway (24,30,31). By contrast, and as expected (13,14,25,27,32), TPX2-depleted extract was inactive in RanGTP-driven MT assembly, while supporting AurA recruitment to and MT nucleation by centrosomes (Fig. 2F, i and iii and Fig.…”
Section: Resultssupporting
confidence: 93%
“…2E), confirming that a minor fraction of endogenous AurA is bound to Cep192 and TPX2 in distinct complexes. Cep192 depletion did not affect the assembly of RanGTP-induced MT asters or AurA targeting to MTs, which are TPX2-dependent processes (13,14,25) (Fig. 2F, iii, quantified in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a microtubule-associated protein, TPX2 tightly adheres to the mitotic spindle in mitotic cells (28). In certain tumors, overexpression of TPX2 results in centrosome amplification and heteroploidy formation (29,30). TPX2 has been demonstrated to be upregulated in salivary gland carcinoma, lung carcinoma and ovarian cancer, with its abnormal expression involved in tumorigenesis and malignant progression (15,16,31).…”
Section: Discussionmentioning
confidence: 99%
“…The Aurora A(S155R) mutation alters the activity and regulation of the kinase, but how could this contribute to the development or survival of a cancerous cell? Studies in human cells and Caenorhabditis elegans in which mutants of TPX2 or TPX-L that did not bind Aurora A replaced the endogenous protein showed that elimination of the interaction resulted in defective mitotic spindles (43,44). In the absence of the interaction with TPX2, Aurora A is localized exclusively to the centrosomes (43,44).…”
Section: Discussionmentioning
confidence: 99%